Xanthone Content in Mangosteen Fruit Juice (Garcinia mangostana L.) and Inhibitory Effect of Mangosteen Fruit Juice on Enzyme Activity (alpha) -Glukosidase - Maris Kurniawati; Chanif Mahdi; Aulanni’am Aulanni'am (Natural B, Journal of Health and Environmental Sciences, 2014)
Glucosidase effects. This study aims to determine the effects of mangosteen rind juice inhibition against α-glucosidase enzyme activity and determine the levels of xanton in mangosteen rind juice. Measuring the level of xanton in mangosteen rind juice using High Performance Liquid Chromatography (HPLC). Enzyme inhibition assay against α-glucosidase activity performed in vitro. The research showed that Mangosteen rind juice samples had a retention time of 8.507 and xanton concentration in each mL juice mangosteen rind of 4.238 μg/mL or 385.272 μg/g juice mangosteen rind. The results showed that xanton in mangosteen rind juice can inhibit the activity of α-glucosidase enzyme. Based on the calculation of percent inhibition mangosteen rind juice against α-glucosidase enzyme activity by 64.71 %.